2.2 The sum of the first terms in an arithmetic series is given by: \( S_{n}=n^{2}-2 n \) Calculate: 2.2 .1 the sum of the first 13 terms. 2.2 .2 the \( 13^{\text {th }} \) term. 2.3 Given the quadratic pattern: \( x ; 6 ; 9 ; y ; 24 ; \ldots \) Calculate the sum of \( x \) and \( y \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To find the sum of the first 13 terms using the formula \( S_{n}=n^{2}-2 n \), we substitute \( n = 13 \): \[ S_{13} = 13^{2} - 2(13) = 169 - 26 = 143. \] So, the sum of the first 13 terms is \( 143 \). Next, we calculate the \( 13^{\text{th}} \) term. The \( n^{\text{th}} \) term can be found using \( T_n = S_n - S_{n-1} \): \[ T_{13} = S_{13} - S_{12} = 143 - (12^{2}-2(12)) = 143 - (144-24) = 143 - 120 = 23. \] So, the \( 13^{\text{th}} \) term is \( 23 \). Now, for the quadratic pattern \( x; 6; 9; y; 24; \ldots \), we notice that the first differences are \( 6 - x \), \( 9 - 6 = 3 \), \( y - 9 \), and \( 24 - y \). The second differences need to be constant. Calculating the second differences: 1. \( (9 - 6) - (6 - x) = 3 - (6 - x) = x - 3 \) 2. \( (y - 9) - (9 - 6) = (y - 9) - 3 = y - 12 \) 3. \( (24 - y) - (y - 9) = (24 - y) - (y - 9) = 33 - 2y \) Setting them equal gives us the following equations: - \( x - 3 = C \) - \( y - 12 = C \) - \( 33 - 2y = C \) From \( x - 3 = y - 12 \), we get \( x = y - 9 \). Now substituting into the third equation: \[ C = x - 3 \] \[ x = y - 9 \implies C = (y - 9) - 3 \implies C = y - 12 \] Setting equations equal, we get \( 33 - 2y = y - 12 \): \[ 33 + 12 = 3y \implies 45 = 3y \implies y = 15 \] With \( y = 15 \), we substitute back to find \( x \): \[ x = 15 - 9 = 6. \] Finally, the sum \( x + y = 6 + 15 = 21. \)